EFFECT OF COMPARISON OF VOLUME FRACTIONS OF PINEAPPLE LEAF FIBER AND BANANA MIDRIB FIBER ON THE MANUFACTURING OF COMPOSITE MATERIALS - Asep Iman Fathurrahman; Kardiman Kardiman; Farradina Choria Suci (Universitas Muhammadiyah Semarang, 2022)
Advances in science and technology in the industrial world today have resulted in the increasing need for materials for the ingredients of a product. Therefore, many new types of materials have been developed that resemble the properties of metals that can absorb or have high strength, such as old composite materials. Composite material is an alloy of two or more materials that have strong mechanical properties from the constituent materials. Composites consist of two main parts, namely the matrix as a binder and filler as a filler of the composite. One of the natural fibers that can be used as reinforcement for composites is pineapple leaf fiber and banana leaf fiber. The matrix used is polyester resin, the composite is made using the ASTM D 638 standard. This study aims to determine the effect of the ratio of fiber volume fractions on the composite of pineapple leaf fiber and banana midrib fiber in order to produce a high performance material. The results of mechanical testing in the tensile test of the composite have the greatest tensile strength and modulus of elasticity at the composition of 15% pineapple leaf fiber and 15% banana midrib fiber, which is 43.25 MPa tensile strength and 2.12 GPa modulus of elasticity. And the largest strain is in the composition of 5% pineapple leaf fiber and 5% banana midrib fiber, which is 4.21%.